Secure cryptosystem based on improved Yang–Gu algorithms in gyrator domain - Tobria, Archana; Singh, Phool (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
A secure cryptosystem based on improved version of Yang–Gu algorithm has been proposed along with lower–upper (LU) decomposition for compression in gyrator transform. Yang–Gu algorithm introduces nonlinearity whereas LU decomposition leads to compression in the proposed scheme. Two random phase masks and binary phase modulators are used in the encryption process. Random phase masks act as public keys and binary phase modulations are applied to generate private keys. Grayscale and medical images are used to validate the proposed cryptosystem against different types of attacks. The statistical attack including information entropy, histogram analysis, correlation distribution plots, and 3-D plots are analyzed for the robustness of the proposed scheme. The quality of the retrieved image is compared with original image using the value of the correlation coefficient. The proposed scheme also showed resistance against data shuffling attack and basic attacks. Key sensitivity analysis demonstrated that the scheme is highly sensitive to its private keys and gyrator transform parameters. Therefore, based on above discussed results, the proposed scheme enhances the security.
Optica Applicata, Vol. 55, 2025, nr 1, s. 97-115
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; improved Yang-Gu mixture amplitude-phase retrieval algorithm; LU decomposition; gyrator transform; image compression